Understanding the implementation of interventions to improve the management of chronic kidney disease in primary care: a rapid realist review. (December 2015) - Tsang, Jung; Blakeman, Tom; Hegarty, Janet; Humphreys, John; Harvey, Gill
Abstract Background Chronic kidney disease (CKD) is common and a significant marker of morbidity and mortality. Its management in primary care is essential for maintenance of cardiovascular health, avoidance of acute kidney injury (AKI) and delay in progression to end-stage renal disease. Although many guidelines and interventions have been established, there is global evidence of an implementation gap, including variable identification rates and low patient communication and awareness. The objective of this study is to understand the factors enabling and constraining the implementation of CKD interventions in primary care. Methods A rapid realist review was conducted that involved a primary literature search of three databases to identify existing CKD interventions in primary care between the years 2000 and 2014. A secondary search was performed as an iterative process and included bibliographic and grey literature searches of reference lists, authors and research groups. A systematic approach to data extraction using Normalisation Process Theory (NPT) illuminated key mechanisms and contextual factors that affected implementation. Results Our primary search returned 710 articles that were narrowed down to 18 relevant CKD interventions in primary care. Our findings suggested that effective management of resources (encompassing many types) was a significant contextual factor enabling or constraining the functioning of mechanisms. Three key intervention features were identified from the many that contributed to successful implementation. Firstly, it was important to frame CKD interventions appropriately, such as within the context of cardiovascular health and diabetes. This enabled buy-in and facilitated an understanding of the significance of CKD and the need for intervention. Secondly, interventions that were compatible with existing practices or patients' everyday lives were readily accepted. In contrast, new systems that could not be integrated were abandoned as they were viewed as inconvenient, generating more work. Thirdly, ownership of the feedback process allowed users to make individualised improvements to the intervention to suit their needs. Conclusions Our rapid realist review identified mechanisms that need to be considered in order to optimise the implementation of interventions to improve the management of CKD in primary care. Further research into the factors that enable prolonged sustainability and cost-effectiveness is required for efficient resource utilisation.